A composite solid electrolyte membrane and a preparation method thereof, a solid-state battery, and an electronic device
Patent Information
- Application Number
- CN202611244088.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]为了解决现有复合固态电解质中填料与聚合物基体间界面阻抗高且结合力弱的问题,本发明提供一种复合固态电解质膜及其制备方法、固态电池和电子设备
1.本发明实施例从共混纤维膜的制备到最终固化完成,从纤维表面经由作为中间层的生长层到孔隙内的填充物,依次形成了纤维与生长层之间的配位键连接以及生长层与填充物之间的配位键连接以及最终固化时前驱体溶液作为填充物通过化学键合方式固定于生长层所围成的孔隙内壁面。本实施例以化学键合替代了传统物理共混法中填料与聚合物基体之间仅靠微弱范德华力或机械嵌套进行的物理结合的方式,化学键合的强度明显优于物理作用力,界面处的结合牢固度得到增强,锂离子在跨界面迁移时因界面结构紧密连接而受到的阻碍减小,同时充放电循环中因体积变化或应力积累导致的界面剥离和相分离风险得到抑制,解决现有固态电解质中填料与聚合物基体间界面阻抗高且结合力弱的问题。
Smart Images

Figure CN122931023A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, and in particular to a composite solid-state electrolyte membrane and its preparation method, as well as solid-state batteries and electronic devices. Background Technology
[0002] With the increasing demands for energy density and safety in electric vehicles and energy storage systems, solid-state batteries are considered a core direction for next-generation battery technology. Among them, composite solid-state electrolytes have attracted much attention due to their combination of the high ionic conductivity of inorganic electrolytes and the good flexibility of polymer electrolytes. However, their overall performance is still constrained by the inherent contradiction between ionic conductivity and mechanical strength.
[0003] Currently, the preparation of composite solid electrolytes mostly employs physical blending methods, where inorganic fillers and polymer matrices are mixed through mechanical stirring or ball milling and then cast into a film. In this process, the filler is randomly dispersed within the matrix, enhancing mechanical strength while providing ion transport pathways through amorphous regions formed at the polymer interface or through its own pores. To achieve certain performance improvements, high filler loadings are often required, but this can easily lead to particle agglomeration and increased film brittleness. The filler's disordered distribution within the matrix makes it difficult to form a continuous and efficient ion transport network; simultaneously, the filler and polymer matrix are bound only by weak physical interactions, resulting in high interfacial impedance and insufficient bonding, making them prone to phase separation and performance degradation during long-term cycling. Summary of the Invention
[0004] To address the issues of high interfacial impedance and weak bonding between fillers and polymer matrices in existing composite solid electrolytes, this invention provides a composite solid electrolyte membrane, its preparation method, a solid-state battery, and an electronic device.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a composite solid electrolyte, the method comprising the following steps: providing a first type of polymer, a second type of polymer, and a co-spinning solvent as raw materials; mixing the first type of polymer, the second type of polymer, and the co-spinning solvent and then performing electrospinning treatment to obtain a blended fiber membrane; providing a surface treatment agent to perform surface treatment on the blended fiber membrane to form active sites on the surface of the blended fiber membrane; providing a metal salt solution to immerse the blended fiber membrane with the active sites in the metal salt solution to allow ion exchange between metal ions and the active sites, thereby transforming the active sites into metal ion growth points; providing an organic ligand solution to remove the blended fiber membrane from the metal salt solution and then immerse it in the organic ligand solution, whereby the organic ligands in the organic ligand solution undergo coordination reactions at the metal ion growth points to form a chain-like growth layer; removing the unreacted organic ligand solution from the blended fiber membrane to obtain a composite framework with a network structure; and providing a precursor solution to immerse the composite framework in the precursor solution and then perform a curing treatment to obtain a composite solid electrolyte membrane.
[0006] Preferably, a cospinning solution is obtained by mixing a first type of polymer, a second type of polymer, and a cospinning solvent. The cospinning solution is then immersed in an electrospinning apparatus. The electrospinning apparatus is used to spin fibers on rollers at an ambient temperature of 20°C-30°C and a voltage of 15kV-25kV. After spinning, the fibers are dried to obtain a blended fiber membrane. The first type of polymer includes polyimide or polyacrylonitrile; and / or the second type of polymer includes polyvinylidene fluoride or cellulose; and / or the cospinning solvent includes any one or a combination of several of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetone, butanone, tetrahydrofuran, ethyl acetate, dichloromethane, chloroform, or acetonitrile. The mass ratio of the first type of polymer to the second type of polymer in the blended fiber membrane is 1:(1-1.5).
[0007] Preferably, the active site includes one or more of carboxyl, hydroxyl, amino, amide, or carbon-carbon double bonds; and / or the surface treatment agent includes any one of an alkaline solvent, an oxidation treatment solution, or a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution; and / or the solute in the metal salt solution includes any one or a combination of cobalt nitrate, zinc nitrate, zinc acetate, copper nitrate, zirconium chloride, zirconium oxynitrate, cobalt sulfate, cobalt chloride, or copper chloride; the solvent of the metal salt solution includes any one or a combination of methanol, ethanol, water, N,N-dimethylformamide, or N,N-dimethylacetamide; wherein the alkaline solvent is any one or a combination of potassium hydroxide or sodium hydroxide; the oxidation treatment solution is any one or a combination of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical / sodium hypochlorite / sodium chlorite combined oxidation system, nitric acid, sulfuric acid, potassium permanganate, or hydrogen peroxide.
[0008] Preferably, the formation of active sites on the surface of the blended fiber membrane includes: when the raw material of the blended fiber membrane includes polyimide, the surface treatment agent is an alkaline solvent, the blended fiber membrane is immersed in the alkaline solvent and treated at 20℃-60℃ for 30 minutes-120 minutes, causing the imide ring of the polyimide to open to generate carboxyl and amide groups, both of which serve as active sites; when the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is an alkaline solvent, the blended fiber membrane is immersed in the alkaline solvent and treated at 40℃-80℃ for 10 minutes-60 minutes, causing carbon-carbon double bonds and oxygen-containing functional groups to be introduced onto the surface of the polyvinylidene fluoride, both of which serve as active sites; when the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is tris(hydroxymethyl)aminomethane-hydrochloric acid buffer. For the first treatment, the blended fiber membrane is immersed in a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution and treated at 40℃-80℃ for 12-48 hours to introduce amino and hydroxyl groups onto the surface of polyvinylidene fluoride (PVDF). Both amino and hydroxyl groups serve as active sites. When the raw material of the blended fiber membrane includes polyacrylonitrile (PAB), an alkaline solvent is used as the surface treatment agent. The blended fiber membrane is immersed in the alkaline solvent and treated at 30℃-70℃ for 1-12 hours to hydrolyze the cyano groups of PAB into carboxyl and amide groups. Both carboxyl and amide groups serve as active sites. When the raw material of the blended fiber membrane includes cellulose, an oxidation treatment solution is used as the surface treatment agent. The blended fiber membrane is immersed in the oxidation treatment solution and treated at 20℃-40℃ for 2-24 hours to partially oxidize the hydroxyl groups of cellulose into carboxyl groups. Both carboxyl and hydroxyl groups serve as active sites.
[0009] Preferably, the process of forming a growth layer by coordination reaction at metal ion growth points includes: providing an alcohol solvent and a metal framework material; mixing the alcohol solvent and the metal framework material to form an organic ligand solution; immersing a composite fiber membrane with metal ion growth points on its surface in the organic ligand solution; reacting at 20°C-40°C for 2-24 hours; the organic ligands in the organic ligand solution undergo coordination reaction with the metal ions on the surface of the composite fiber membrane to form a growth layer at the metal ion growth points; wherein the metal framework material includes any one or a combination of several of the following: zeolite imidazole ester skeleton-8, zeolite imidazole ester skeleton-67, copper benzotricarboxylic acid skeleton-1, zirconium terephthalic acid skeleton-66, zeolite imidazole ester skeleton-7, and zeolite imidazole ester skeleton-90.
[0010] Preferably, obtaining a composite solid electrolyte membrane by immersing the precursor solution into the composite skeleton and then curing it includes: mixing a monomer containing polar groups, a thermal initiator, a lithium salt, a cosolvent, and a plasticizer to obtain a precursor solution; the composite fiber skeleton with a network structure has pores; immersing the composite fiber skeleton in the precursor solution and allowing it to stand at 20℃-40℃ for 0.5 hours to 48 hours to allow at least part of the precursor solution to penetrate into the pores of the composite fiber skeleton; after standing, thermally curing the composite fiber skeleton at 50℃-90℃ for 4 hours to 24 hours to allow the monomer containing polar groups in the precursor solution to polymerize and solidify in the pores to obtain the composite solid electrolyte membrane.
[0011] Preferably, the monomers containing polar groups include any one or a combination of several of the following: methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, acrylonitrile, vinyl acetate, fluorinated acrylates, or hexafluorobutyl acrylate; the thermal initiator includes any one or a combination of several of the following: azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azodicyclohexylformonitrile, benzoyl peroxide, or diisopropyl peroxide. The lithium salt comprises any one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium dioxalate borate, or lithium trifluoromethanesulfonate; the lithium salt concentration is preferably 0.5 mol / L to 2 mol / L; the cosolvent comprises any one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or acetonitrile; the plasticizer comprises any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, succinate, or glutaronitrile.
[0012] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: a composite solid electrolyte membrane, prepared by the method described above for preparing a composite solid electrolyte, the composite solid electrolyte membrane comprising a composite framework and a filler, the composite framework comprising a fiber membrane layer and a growth layer, the fiber membrane layer being composed of several overlapping fibers forming a three-dimensional network structure, the fiber membrane layer having pores, the growth layer covering the surface of the fibers, the growth layer being a layered structure of a metal-organic framework material anchored to the surface of the fibers by coordination bonds; complexation anchoring points are provided on the inner wall surface of the pores, at least a portion of the pores are provided with the filler, the filler filling at least a portion of the pores, the filler being a mixture of materials containing polar groups, fixed to the inner wall surface of the pores enclosed by the growth layer by chemical bonding between the polar groups and the coordination bonds in the growth layer.
[0013] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: a solid-state battery, comprising a positive electrode, a negative electrode, and the above-mentioned composite solid-state electrolyte membrane, wherein the composite solid-state electrolyte membrane is disposed between the positive electrode and the negative electrode.
[0014] To solve the above-mentioned technical problems, the present invention provides another technical solution as follows: an electronic device, the electronic device including a device body and the above-mentioned solid-state battery, wherein the solid-state battery is disposed in the device body.
[0015] Compared with the prior art, the composite solid electrolyte membrane and its preparation method provided by the present invention have the following beneficial effects: 1. This invention, from the preparation of the blended fiber membrane to its final curing, sequentially forms coordination bonds between the fiber and the growth layer, and between the growth layer and the filler, from the fiber surface through the growth layer (which serves as an intermediate layer) to the filler within the pores. During final curing, the precursor solution, acting as the filler, is chemically bonded to the inner wall of the pores enclosed by the growth layer. This embodiment replaces the physical bonding between the filler and the polymer matrix, which relies solely on weak van der Waals forces or mechanical nesting, in traditional physical blending methods with chemical bonding. The strength of chemical bonding is significantly superior to physical forces, enhancing the interfacial bonding strength. This reduces the resistance to lithium ion migration across the interface due to the tightly connected interfacial structure. Simultaneously, it suppresses the risk of interfacial delamination and phase separation caused by volume changes or stress accumulation during charge-discharge cycles, thus solving the problems of high interfacial impedance and weak bonding between the filler and the polymer matrix in existing solid electrolytes.
[0016] 2. In the composite solid electrolyte membrane provided in this embodiment of the invention, the fiber membrane layer consists of a three-dimensional network structure composed of several overlapping fibers, which provides a continuous mechanical support framework for the entire electrolyte membrane. The growth layer, as a metal-organic framework material, is a layered structure anchored to the fiber surface through coordination bonds, uniformly covering the surface of each fiber. Complexation anchoring points are provided on the inner wall of the pores. The filler fills at least part of the pores, and the filler is a mixture of materials containing polar groups, which are fixed to the inner wall of the pores through chemical bonding between the polar groups and the coordination bonds in the growth layer. Structurally, the solid electrolyte membrane achieves chemical anchoring between the fibers and the growth layer through coordination bonds between the metal-organic framework material and the active sites on the fiber surface, and chemical bonding between the growth layer and the filler is achieved through coordination between the polar groups of the polymer segments in the filler and the metal sites of the metal-organic framework in the growth layer. Since the strength of chemical bonding is significantly better than that of physical forces, there are no physical interfaces between the filler and the growth layer, or between the growth layer and the fiber, that allow for relative sliding or peeling. Therefore, the resistance encountered by lithium ions during cross-interface migration is reduced due to the tight connection of the interfaces.
[0017] 3. The solid-state battery provided in this embodiment of the invention has a composite solid electrolyte membrane with good mechanical strength and flexibility, which can adapt to the small deformations during battery assembly and use, reduce the risk of internal short circuits, and improve the safety of the solid-state battery.
[0018] 4. The electronic device provided in the embodiments of the present invention has a solid-state battery with a composite solid-state electrolyte membrane. The composite solid-state electrolyte membrane constructs a continuous ion transport channel with low impedance and high binding force and a stable mechanical support network through multiple chemical bonds between the fiber and the growth layer and between the growth layer and the filler, so that the solid-state battery of the electronic device has high energy efficiency and high safety. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a schematic diagram of the process of the composite solid electrolyte membrane provided in the first embodiment of the present invention.
[0021] Figure 2a This is a partial structural schematic diagram of the composite skeleton of the present invention.
[0022] Figure 2bThis is a schematic diagram of the structure of PI (polyimide) and PVDF (polyvinylidene fluoride) raw materials in this invention.
[0023] Figure 3 This is a schematic diagram of the process for forming active sites on the surface of a PI (polyimide) and PVDF (polyvinylidene fluoride) blended fiber membrane according to the present invention.
[0024] Figure 4 This is a schematic diagram of the process of transforming active sites on a PI (polyimide) and PVDF (polyvinylidene fluoride) blended fiber membrane into metal ion growth points according to the present invention.
[0025] Figure 5 This is a schematic diagram of the process of forming a chain-like growth layer on a PI (polyimide) and PVDF (polyvinylidene fluoride) blended fiber membrane according to the present invention. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0027] In the embodiments provided by this invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined based on A. However, it should also be understood that determining B based on A does not mean determining B solely based on A; B can also be determined based on A and / or other information.
[0028] It should be understood that the phrase "one embodiment" or "an embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Those skilled in the art should also recognize that the embodiments described in the specification are optional embodiments, and the actions and modules involved are not necessarily essential to the invention.
[0029] In various embodiments of the present invention, it should be understood that the sequence number of each process does not necessarily imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0030] The flowcharts and block diagrams in the accompanying drawings illustrate the architecture, functionality, and operation of possible implementations of systems, methods, and computer program products according to various embodiments of this application. In this regard, each block in a flowchart or block diagram may represent a module, segment, or portion of code containing one or more executable instructions for implementing a specified logical function. It should also be noted that in some alternative implementations, the functions indicated in the blocks may occur in a different order than those indicated in the drawings. For example, two consecutively indicated blocks may actually be executed substantially in parallel, or they may sometimes be executed in reverse order, depending on the functions involved. It is particularly important to note that each block in a block diagram and / or flowchart, and combinations of blocks in block diagrams and / or flowcharts, can be implemented using a dedicated hardware-based system that performs the specified function or operation, or using a combination of dedicated hardware and computer instructions.
[0031] Please see Figure 1 The first embodiment of the present invention provides a method for preparing a composite solid electrolyte, the method comprising the following steps: Step S1: Provide a first type of polymer, a second type of polymer and a co-spinning solvent as raw materials, mix the first type of polymer, the second type of polymer and the co-spinning solvent and then perform electrospinning treatment to obtain a blended fiber membrane; Step S2: Provide a surface treatment agent to treat the surface of the blended fiber membrane to form active sites on the surface of the blended fiber membrane; Step S3: Provide a metal salt solution and immerse the blended fiber membrane that forms active sites into the metal salt solution so that metal ions exchange with the active sites and the active sites become metal ion growth points. Step S4: Provide an organic ligand solution. After the blended fiber membrane is removed from the metal salt solution, it is immersed in the organic ligand solution. The organic ligands in the organic ligand solution undergo coordination reactions at the metal ion growth points to form a chain-like growth layer. Step S5: Remove the unreacted organic ligand solution from the blended fiber membrane to obtain a composite framework with a network structure; and Step S6: Provide a precursor solution, immerse the composite skeleton in the precursor solution and then perform a curing treatment to obtain a composite solid electrolyte membrane.
[0032] Understandably, this example first involves blending and spinning a first type of polymer with a second type of polymer, utilizing the two polymers to construct multiphase interface regions within and on the surface of the fiber during spinning. The multiphase interface in blend spinning refers to the separation of microphases caused by the rapid evaporation of solvents during electrospinning of two thermodynamically incompatible polymers, such as polyimide and polyvinylidene fluoride. Initially, the molecules of the two polymers tend to aggregate separately, resulting in microphase separation. Ultimately, each fiber exhibits both microregions enriched in polyimide and microregions enriched in polyvinylidene fluoride. The boundary region formed by the interweaving of these two chemically different microregions is the multiphase interface. The existence of this multiphase interface provides reaction sites for subsequent surface treatment steps, allowing surface treatment agents to introduce corresponding active functional groups to different polymer components. During ion exchange, metal ions are anchored to the active sites through complexation, transforming the active sites into metal ion growth points. When the fiber membrane is immersed in the organic ligand solution, the organic ligands undergo coordination reactions at the metal ion growth points. Since the metal ions have already formed complexes with the active sites on the fiber surface through ion exchange, the growth layer generated by the coordination reaction can be firmly bonded to the fiber surface by chemical bonding. Therefore, the growth layer generated by the coordination reaction is formed by a large number of organic ligand molecules coordinating with the densely distributed metal ion growth points on the fiber surface one by one. Each organic ligand chain segment is fixed to the fiber surface with an independent anchoring point. The numerous chain segments are connected and extended to each other in space. From a macroscopic perspective, this is manifested as a continuous layered structure growing in situ on the fiber surface, which enables the growth layer to be firmly bonded to the fiber surface by chemical bonding, rather than being loosely attached.
[0033] Furthermore, the blended fiber membrane forming the growth layer is dried to evaporate and remove unreacted organic ligand solution, resulting in a uniform growth layer coating the fiber surface. Next, the composite framework is immersed in a precursor solution, allowing the precursor solution to fully penetrate the fiber gaps and the microscopic channels of the growth layer through the network pore structure of the composite framework. During curing, the precursor solution polymerizes within a confined space. Since the growth layer is chemically bonded to the fiber surface through the aforementioned coordination reaction, the polymerized filler and the growth layer achieve interfacial bonding through the interaction of polar groups and coordination sites. Therefore, in this embodiment, from the preparation of the blended fiber membrane to the final curing, coordination bonds are sequentially formed between the fiber surface, through the growth layer (as an intermediate layer), and to the filler within the pores. Finally, during curing, the precursor solution, as the filler, is chemically bonded to the inner wall of the pores enclosed by the growth layer. This embodiment replaces the physical bonding between the filler and the polymer matrix, which relies solely on weak van der Waals forces or mechanical nesting, in the traditional physical blending method with chemical bonding. The strength of chemical bonding is significantly better than that of physical forces, and the bonding strength at the interface is enhanced. The resistance encountered by lithium ions during cross-interface migration due to the tight connection of the interface structure is reduced. At the same time, the risk of interface peeling and phase separation caused by volume changes or stress accumulation during charge-discharge cycles is suppressed, thus solving the problem of high interfacial impedance and weak bonding between the filler and the polymer matrix in existing solid electrolytes.
[0034] Further, the first type of polymer includes polyimide or polyacrylonitrile; the second type of polymer includes polyvinylidene fluoride or cellulose; the co-spinning solvent includes any one or a combination of several of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetone, butanone, tetrahydrofuran, ethyl acetate, dichloromethane, chloroform or acetonitrile; wherein the mass ratio of the first type of polymer and the second type of polymer in the blended fiber membrane is 1:(1-1.5).
[0035] Understandably, the first type of polymer is selected as polyimide or polyacrylonitrile, and the second type of polymer is selected as polyvinylidene fluoride or cellulose. After the two types of polymers are mixed in a co-spinning solvent system and electrospinned, microphase separation occurs during fiber forming due to differences in their solubility and molecular structure. This results in a multiphase interface structure with alternating enriched phases of the first and second types of polymers. In the first type of polymer, the imide ring of polyimide can be ring-opened to generate carboxyl groups under subsequent alkaline treatment, and the cyano groups of polyacrylonitrile can be converted into carboxyl and amide groups under alkaline hydrolysis. Both of these groups can serve as active sites for the nucleation of metal-organic frameworks. In the second type of polymer, polyvinylidene fluoride can be treated with alkaline to introduce carbon-carbon double bonds and oxygen-containing functional groups, and cellulose itself contains natural hydroxyl groups or can be converted into carboxyl groups through oxidation, which can also serve as active sites. The active sites provided by the two types of polymers are chemically complementary, avoiding the limitation that a single polymer can only provide a single type of nucleation site. This allows subsequent metal ions to uniformly complex and anchor to different chemical microregions on the fiber surface through ion exchange, thereby promoting the uniform and dense coating of the growth layer generated by the coordination reaction.
[0036] This example further specifies the mass ratio of the first type of polymer to the second type of polymer as 1:(1-1.5). The first type of polymer phase provides rigidity and heat resistance support, while the second type of polymer phase provides flexibility and a polar interface. The first type of polymer has a relatively high molecular chain rigidity and a high glass transition temperature, which can provide tensile strength and dimensional thermal stability for the blended fiber membrane, preventing shrinkage deformation or structural collapse of the fiber membrane during subsequent surface treatment, ion exchange, coordination reaction, and thermosetting steps. The second type of polymer has better molecular chain flexibility, which can compensate for the brittleness defects brought by the rigid polymer, giving the fiber membrane bending flexibility and avoiding membrane cracking due to excessive rigidity. The two types of polymers form a multiphase continuous network with alternating rigid and flexible phases within the same fiber through blend spinning. The rigid phase undertakes the structural support function, while the flexible phase undertakes the stress buffer function. Together, they enable the fiber membrane to maintain sufficient mechanical strength while possessing good flexibility. For example, in the surface treatment step, the fiber membrane needs to be immersed in an alkaline solution or oxidizing solution. The rigid phase ensures that the fiber membrane does not undergo severe swelling and deformation, while the flexible phase alleviates local stress concentration caused by chemical treatment. In the ion exchange and coordination reaction steps, the fiber membrane needs to be immersed, and the synergy of rigid and flexible phases ensures that the fiber membrane maintains its structural integrity and does not break in a wet state. In the curing step, the rigid phase ensures that the fiber membrane does not undergo significant thermal shrinkage during heating, while the flexible phase adapts to the slight acoustic expansion caused by temperature changes. Ultimately, the synergistic cooperation of the rigid and flexible phases allows the composite framework to maintain a rollable film shape while possessing a growth layer, enabling the solid electrolyte membrane to have mechanical maneuverability in addition to its ion conduction function.
[0037] Optionally, the mass ratio of the first type of polymer to the second type of polymer can also be 1:1, 1:1.3 or 1:1.5.
[0038] Specifically, in step S1 above, the electrospinning process to obtain the blended fiber membrane includes: The first type of polymer, the second type of polymer and the co-spinning solvent are mixed to obtain a co-spinning solution. The co-spinning solution is immersed in an electrospinning device. The electrospinning device is used to spin on the rollers of the electrospinning device at an ambient temperature of 20℃-30℃ and a voltage of 15kV-25kV. After spinning, the mixture is dried to obtain a blended fiber membrane.
[0039] Understandably, in this example, a cospinning solution is obtained by mixing the first type of polymer, the second type of polymer, and a cospinning solvent. The electrospinning equipment is equipped with nozzles and rollers. The cospinning solution is sprayed from the nozzles and electrospinned on the rollers. The ambient temperature is controlled within the range of 20℃-30℃ to maintain suitable viscosity and surface tension of the cospinning solution within this temperature range. This avoids excessively low temperatures that would result in excessively high solution viscosity, making it difficult for the jet to be sprayed, and also avoids excessively high temperatures that would cause the solvent to evaporate too quickly, leading to premature solidification or defects in the jet before it reaches the rollers. The voltage is set within the range of 15kV-25kV to provide sufficient electric field force to overcome the surface tension of the solution and achieve sufficient stretching and refinement, allowing the jet to fully extend during flight and form fibers of uniform diameter. It should be noted that too low a voltage will result in coarser fiber diameters, while too high a voltage will cause fiber splashing or breakage. The roller rotates continuously during spinning, causing a directional traction force in the direction of roller rotation during jet deposition, guiding the fibers to align to a certain extent along the circumference of the roller. After spinning, drying is performed to remove residual solvent, further solidifying and shaping the internal structure of the fibers and preventing solvent residue. For example, please refer to... Figure 2b and Figure 3 , Figure 2b This demonstrates that the raw materials for polyimide and polyethylene are in a fibrous form, and that the fibrous polyimide and polyethylene co-spun into fibers such as... Figure 3 The fiber interwoven structure shown should be noted that Figure 2b and Figure 3 This is merely a simple illustration, where the dashed lines represent omitted fiber structures.
[0040] Optionally, the electrospinning equipment can also be used in environments with temperatures ranging from 20°C to 23°C, 21°C to 24°C, or 23°C to 25°C, and with voltages ranging from 15kV to 20kV, 19kV to 22kV, or 17kV to 25kV.
[0041] Specifically, the active site includes one or more of carboxyl, hydroxyl, amino, amide, or carbon-carbon double bonds; The surface treatment agent includes any one of an alkaline solvent, an oxidation treatment solution, or a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, wherein the alkaline solvent is any one or a combination of potassium hydroxide or sodium hydroxide; the oxidation treatment solution is any one or a combination of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical / sodium hypochlorite / sodium chlorite combined oxidation system, nitric acid, sulfuric acid, potassium permanganate, and hydrogen peroxide.
[0042] Understandably, the surface treatment agents used in this example are selectively applied based on the specific components of the first and second polymer classes in the blended fiber membrane, to introduce one or more active sites from carboxyl, hydroxyl, amino, amide, or carbon-carbon double bonds onto the fiber surface. Alkaline solvents such as potassium hydroxide or sodium hydroxide are suitable for treating polyimide-containing fiber membranes, causing the imide ring to open and generate carboxyl and amide groups. They are also suitable for treating polyvinylidene fluoride-containing fiber membranes, introducing carbon-carbon double bonds and oxygen-containing functional groups onto their surface, and for treating polyacrylonitrile-containing fiber membranes, hydrolyzing cyano groups into carboxyl and amide groups. Tris(hydroxymethyl)aminomethane-hydrochloric acid buffer is suitable for introducing amino and hydroxyl groups onto the polyvinylidene fluoride surface. Oxidation treatment solutions are suitable for treating cellulose-containing fiber membranes, partially oxidizing natural hydroxyl groups to carboxyl groups. Therefore, the selection of surface treatment agents is matched to the chemical composition of the two polymers in the blended fiber membrane, ensuring that each polymer component can effectively generate the corresponding active functional groups under the appropriate treatment conditions.
[0043] Specifically, the chemical type of the active site directly determines its ability to subsequently complex and anchor with metal ions. Carboxyl, hydroxyl, amino, and amide groups all contain oxygen or nitrogen atoms that can provide lone pairs of electrons, enabling them to form stable coordination complexes with metal ions. The presence of carbon-carbon double bonds introduces an additional polar environment on the fiber surface, helping to regulate the initial adsorption distribution of metal ions. Compared to single active sites, this example simultaneously constructs multiple chemical types of active sites on the surface of the blended fiber membrane. Because these active sites originate from different polymer components and are distributed across the fiber surface, metal ions can select suitable sites for anchoring during ion exchange based on their coordination preferences, promoting uniform dispersion of metal ions on the fiber surface.
[0044] Specifically, in step S2 above, this example sets matching surface treatment methods, temperature ranges and treatment times for the specific polymer components contained in the blended fiber membrane, so as to ensure that each type of polymer can efficiently generate the corresponding active sites under the corresponding conditions.
[0045] In one embodiment, when the raw material of the blended fiber membrane includes polyimide, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 20°C-60°C for 30-120 minutes, causing the imide ring of the polyimide to open and generate carboxyl and amide groups, both of which serve as active sites. Optionally, the treatment temperature can also be 20°C-40°C, 30°C-50°C, or 40°C-60°C, and the treatment time can also be 30-80 minutes, 40-100 minutes, or 60-120 minutes.
[0046] Understandably, when the blended fiber membrane contains polyimide, this example uses an alkaline solvent for treatment, causing the imide rings on the polyimide molecular chain to undergo a ring-opening reaction to generate carboxyl and amide groups. Both carboxyl and amide functional groups can provide oxygen or nitrogen atoms that offer lone pair electrons, which can serve as complexation anchoring sites for metal ions.
[0047] In one embodiment, when the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 40°C-80°C for 10-60 minutes to introduce carbon-carbon double bonds and oxygen-containing functional groups onto the surface of the polyvinylidene fluoride. Both carbon-carbon double bonds and oxygen-containing functional groups serve as active sites. Optionally, the treatment temperature can also be 40°C-60°C, 50°C-70°C, or 60°C-80°C, and the treatment time can also be 10-30 minutes, 20-50 minutes, or 40-60 minutes.
[0048] Understandably, when the blended fiber membrane contains polyvinylidene fluoride (PVDF), this example uses an alkaline solvent to treat it at 40°C-80°C, causing a defluorination reaction on the PVDF surface and introducing carbon-carbon double bonds and oxygen-containing functional groups as active sites. The 40°C-80°C temperature range is higher than the treatment temperature of polyimide to meet the activation energy required for the defluorination reaction, while the shorter treatment time avoids excessive etching of the PVDF by the alkaline solvent. The oxygen atoms in the oxygen-containing functional groups can provide lone pairs of electrons to form complexes and anchor metal ions, while the carbon-carbon double bonds, as unsaturated groups, can weakly interact with metal ions through their π-electron clouds. This assists the oxygen-containing functional groups in guiding the uniform adsorption and distribution of metal ions on the fiber surface, preventing excessive aggregation of metal ions in localized areas and providing uniformly distributed nucleation sites for subsequent coordination reactions. When the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is tris(hydroxymethyl)aminomethane-hydrochloric acid buffer. The blended fiber membrane is immersed in tris(hydroxymethyl)aminomethane-hydrochloric acid buffer to introduce amino and hydroxyl groups onto the surface of polyvinylidene fluoride. Both amino and hydroxyl groups serve as active sites.
[0049] In one embodiment, when the raw material of the blended fiber membrane includes polyacrylonitrile, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 30°C-70°C for 1-12 hours to hydrolyze the cyano groups of polyacrylonitrile into carboxyl and amide groups. Both carboxyl and amide groups serve as active sites. Optionally, the treatment temperature can also be 30°C-40°C, 50°C-60°C, or 40°C-70°C, and the treatment time can also be 1-8 hours, 4-10 hours, or 6-12 hours.
[0050] Understandably, when the blended fiber membrane contains polyacrylonitrile, this example uses an alkaline solvent to treat it at 30°C-70°C, causing the cyano groups on the polyacrylonitrile molecular chain to hydrolyze and convert into carboxyl and amide groups. The temperature range of 30°C-70°C is wider than that for the ring-opening reaction of polyimide, and the temperature is controlled at 70°C to avoid excessive degradation of the polyacrylonitrile backbone. The generated carboxyl and amide groups both contain oxygen or nitrogen atoms that can provide lone pair electrons, serving as complexation anchoring sites for metal ions.
[0051] In one embodiment, when the raw material of the blended fiber membrane includes cellulose, the surface treatment agent is an oxidation treatment solution. The blended fiber membrane is immersed in the oxidation treatment solution and treated at 20°C-40°C for 2-24 hours to oxidize the hydroxyl groups of cellulose to carboxyl groups. Both carboxyl and hydroxyl groups serve as active sites.
[0052] Understandably, when blended fiber membranes contain cellulose, an oxidation treatment solution is used at 20℃-40℃ to partially oxidize the numerous naturally occurring hydroxyl groups on the cellulose molecular chain into carboxyl groups. Cellulose itself is rich in hydroxyl groups, and the oxygen atoms of the hydroxyl groups can provide lone pairs of electrons to coordinate with metal ions. The carboxyl groups further generated after oxidation also possess coordination ability, resulting in the presence of both hydroxyl and carboxyl groups as active sites on the final fiber surface. Carboxyl groups generally have a stronger complexing ability for metal ions than hydroxyl groups; the coexistence of both on the fiber surface facilitates the dispersion of metal ions.
[0053] Please combine Figure 4 and Figure 5When a blended fiber membrane contains two polymers simultaneously, such as polyimide and polyvinylidene fluoride (PVDF), after surface treatment, the polyimide component undergoes ring-opening in an alkaline solvent to generate carboxyl and amide groups, while the PVDF component undergoes defluorination in an alkaline solvent, introducing carbon-carbon double bonds and oxygen-containing functional groups. Due to microphase separation during electrospinning, both polyimide-enriched and PVDF-enriched microregions exist simultaneously on the fiber surface. These two types of active sites are distributed within their respective polymer-enriched microregions, forming an alternating arrangement. The carboxyl, amide, and oxygen-containing functional groups all contain oxygen or nitrogen atoms that can provide lone pairs of electrons, serving as complexation anchoring sites for metal ions. Furthermore, the π-electron cloud of the carbon-carbon double bond helps guide the initial adsorption distribution of metal ions. Compared to single polyimide fiber membranes which can only provide carboxyl and amide groups, or single polyvinylidene fluoride fiber membranes which can only provide carbon-carbon double bonds and oxygen-containing functional groups, the coexistence of two types of sites on the same fiber surface and their distribution in different chemical microregions allows metal ions to select suitable sites for anchoring according to their own coordination preferences, avoiding local oversaturation of a single type of site or metal ion aggregation, and achieving uniform dispersion of metal ions on the fiber surface.
[0054] It should be noted that the present invention Figure 4 and Figure 5 The dashed lines in the text represent the fibrous structures of PI (polyimide) and PVDF (polyvinylidene fluoride), which are omitted from the description. Figure 3 After PI (polyimide) and PVDF (polyvinylidene fluoride) are co-spun into a blended fiber membrane, active sites are formed on the surface of the blended fiber membrane. Figure 4 This describes the process by which active sites on a PI (polyimide) and PVDF (polyvinylidene fluoride) blended fiber membrane are transformed into metal ion growth sites. The PI and PVDF fiber structures of the blended fiber membrane possess active sites such as -OH and -COOH on their surfaces. Metal ions exchange ions with these active sites, transforming them into metal ion growth sites –OZn. 2+ and -COOZn 2+ . Figure 5 The term "MOF" refers to the formation of chain-like growth layers on a PI (polyimide) and PVDF (polyvinylidene fluoride) blended fiber membrane. Specifically, organic ligands in the organic ligand solution undergo coordination reactions at the metal ion growth sites to form chain-like growth layers, resulting in a network-structured composite framework. Organic ligands adhere to the PI fiber structure to form a PI@MOF framework, and organic ligands adhere to the PVDF fiber structure to form a PVDF@MOF framework. Together, the PI@MOF and PVDF@MOF frameworks constitute the network-structured composite framework. Please refer to the attached diagram for the structure of the network-structured composite framework. Figure 2a .
[0055] Specifically, the solute in the metal salt solution includes any one or a combination of several of cobalt nitrate, zinc nitrate, zinc acetate, copper nitrate, zirconium chloride, zirconium oxynitrate, cobalt sulfate, cobalt chloride, or copper chloride; the solvent of the metal salt solution includes one or a combination of several of methanol, ethanol, water, N,N-dimethylformamide, or N,N-dimethylacetamide.
[0056] Understandably, in this example, the solute in the metal salt solution is selected from one or more combinations of cobalt nitrate, zinc nitrate, zinc acetate, copper nitrate, zirconium chloride, zirconium oxynitrate, cobalt sulfate, cobalt chloride, or copper chloride. The solute ionizes in the solution to release corresponding cobalt, zinc, copper, or zirconium ions, providing a source of metal ions for subsequent coordination reactions. Different metal ions have different coordination configuration preferences and coordination numbers. For example, cobalt and zinc ions often form tetrahedral or octahedral coordination structures with nitrogen-containing ligands, copper ions tend to form planar tetragonal coordination, and zirconium ions prefer to form high-coordination-number clusters with oxygen-containing ligands. Selecting different metal ions can adapt to the complexation requirements of different types of active sites. The oxygen atoms in carboxyl and amide groups have a strong affinity for zirconium and copper ions, while the nitrogen atoms in amino groups are more suitable for coordination with cobalt and zinc ions. Therefore, suitable metal salt solutes can be flexibly selected according to the specific types of active sites on the surface of the blended fiber membrane. The solvent for the metal salt solution is selected from one or a combination of methanol, ethanol, water, N,N-dimethylformamide, or N,N-dimethylacetamide. The solvent exhibits good solubility for the selected metal salt and suitable wettability for the blended fiber membrane, without causing swelling or damage to the fiber structure. The choice of solvent directly affects the diffusion and distribution behavior of metal ions on the fiber surface. Methanol and ethanol, with their lower boiling points, evaporate quickly, facilitating the rapid accumulation of metal ions on the fiber surface. N,N-dimethylformamide and N,N-dimethylacetamide, with their higher boiling points, provide a longer wetting time, allowing the metal ions to fully penetrate to the various chemical microregions and contact the active sites on the fiber surface.
[0057] Furthermore, in step S4 above, the formation of a growth layer by a coordination reaction at the metal ion growth site includes: An alcohol solvent and a metal framework material are provided. The alcohol solvent and the metal framework material are mixed to form an organic ligand solution. A composite fiber membrane with metal ion growth points on its surface is immersed in the organic ligand solution and reacted at 20℃-40℃ for 2 hours-24 hours. The organic ligands in the organic ligand solution undergo a coordination reaction with the metal ions on the surface of the composite fiber membrane to form a growth layer on the metal ion growth points. The metal framework material includes any one or a combination of several of the following: zeolite imidazole ester framework-8, zeolite imidazole ester framework-67, copper benzotricarboxylic acid framework-1, zirconium terephthalic acid framework-66, zeolite imidazole ester framework-7, and zeolite imidazole ester framework-90.
[0058] Understandably, in this example, the growth layer is formed by immersing a blended fiber membrane with metal ion growth points already loaded on its surface into an organic ligand solution. A temperature range of 20℃-40℃ provides the activation energy required for the coordination reaction, preventing excessively high temperatures from causing an overly rapid coordination reaction and resulting in an uneven growth layer structure. The reaction time is adjusted according to the density and distribution of the metal ion growth points to ensure sufficient coordination reaction between the organic ligand and the metal ions, allowing the growth layer to achieve a certain coverage and thickness on the fiber surface.
[0059] Specifically, the metal framework materials used in this example include one or more combinations of zeolite imidazole ester framework-8, zeolite imidazole ester framework-67, copper phenyltricarboxylic acid framework-1, zirconium terephthalic acid framework-66, zeolite imidazole ester framework-7, or zeolite imidazole ester framework-90. For example, the zeolite imidazole ester framework series contains imidazole groups, whose nitrogen atoms can participate in coordination; copper phenyltricarboxylic acid framework-1 contains carboxyl groups; and zirconium terephthalic acid framework-66 contains terephthalate ions. Different ligands have different coordination affinities with different metal ions. Therefore, when selecting a metal framework material, it is necessary to match it with the metal salt solute used in the aforementioned steps so that the organic ligands can effectively coordinate with the metal ions already anchored on the fiber surface, transforming the metal ion growth points one by one into connecting nodes of the chain-like growth layer. Organic ligands grow chain by chain at the growth sites of metal ions through coordination bonds. Numerous chain segments extend and connect with each other in space, eventually forming a continuous coating growth layer on the fiber surface. This growth layer is fixed to the fiber surface through the dual chemical action of complexation bonds between metal ions and active sites and coordination bonds between organic ligands and metal ions.
[0060] Further, please refer to Figure 2a In step S6 above, the composite solid electrolyte membrane is obtained by immersing the precursor solution into the composite framework and then performing a curing treatment. A precursor solution is obtained by mixing a monomer containing a polar group, a thermal initiator, a lithium salt, a cosolvent, and a plasticizer. The composite fiber skeleton with a mesh structure has pores. The composite fiber skeleton is immersed in a precursor solution and left to stand at 20℃-40℃ for 0.5 hours-48 hours to allow at least a portion of the precursor solution to permeate into the pores of the composite fiber skeleton; and After standing, the composite fiber skeleton is heat-cured at 50℃-90℃ for 4-24 hours, so that the monomers containing polar groups in the precursor solution are polymerized and cured in the pores to obtain a composite solid electrolyte membrane.
[0061] Alternatively, the processing temperature can be 20℃-30℃, 25℃-35℃ or 30℃-40℃, and the processing time can be 4 hours-18 hours, 10 hours-15 hours or 14 hours-24 hours.
[0062] Understandably, in this example, a precursor solution is obtained by mixing a monomer containing polar groups, a thermal initiator, a lithium salt, a co-solvent, and a plasticizer. The composite framework with a network structure is then immersed in this precursor solution and allowed to stand at 20°C-40°C for 0.5-48 hours. This allows the precursor solution to spontaneously penetrate into the micron-scale gaps between fibers and the nanoscale pores of the metal-organic framework material in the growth layer through the capillary force of the porous structure within the composite framework. The standing temperature is controlled within the range of 20°C-40°C to ensure that the precursor solution has a suitable viscosity to smoothly wet pores of all sizes, avoiding excessively high temperatures that would cause the solvent to evaporate too quickly and concentrate and precipitate the precursor solution before sufficient penetration. The standing time is adjusted according to the density of the growth layer in the composite framework; the denser the growth layer and the higher the loading, the longer the required immersion time, ensuring that the precursor solution fully penetrates into all pores. The curing treatment after standing can be either photocuring or thermocuring.
[0063] For example, consider thermosetting: the composite fiber framework is thermoset at 50℃-90℃ for 4-24 hours. Under heating conditions, the thermal initiator undergoes homolytic decomposition to generate active free radicals. These free radicals attack the unsaturated double bonds in monomers containing polar groups, initiating a chain addition polymerization reaction. This causes the monomers to simultaneously transform into polymer segments within the fiber gaps, growth layer gaps, and nanopores. After polymerization, the monomers in the precursor solution form a three-dimensional continuous polymer electrolyte network within the pores of the composite framework at various scales. More importantly, the polymer segments formed contain polar groups such as carbonyl, ester, or nitrile groups. The oxygen or nitrogen atoms in these polar groups contain lone pairs of electrons, which can act as coordination sites for the metal-organic framework in the growth layer. This allows the polymer segments to be fixed to the inner walls of the pores through coordination bonds. This chemical bonding method prevents the polymer from separating from the fiber framework, ensuring the polymer segments are tightly attached to the inner walls of the metal-organic framework pores.
[0064] Specifically, monomers containing polar groups include any one or a combination of several of the following: methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, acrylonitrile, vinyl acetate, fluorinated acrylates, or hexafluorobutyl acrylate. These monomers all contain polar functional groups such as carbonyl, ester, nitrile, or fluorinated ester groups. These polar groups are retained on the polymer segments formed after polymerization, serving as active sites for coordination anchoring with metal sites in the metal-organic framework.
[0065] Specifically, thermal initiators include any one or a combination of several of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobiscyclohexylformonitrile, benzoyl peroxide, or diisopropyl peroxide dicarbonate. Azo initiators are chemically inert to the metal sites of the metal-organic framework and will not be adsorbed or catalytically decomposed by the metal sites, thus ensuring that they can still effectively decompose to generate free radicals to initiate polymerization in a pore-confined environment.
[0066] Specifically, the lithium salt includes any one or a combination of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium dioxalate borate, or lithium trifluoromethanesulfonate; the lithium salt concentration is preferably 0.5 mol / L-2 mol / L; the lithium salt provides a sufficient source of charge carriers for the solid electrolyte, and this concentration range ensures that a sufficient number of lithium ions participate in the conduction while avoiding excessively high concentrations that may lead to lithium salt precipitation or affect the normal progress of the polymerization reaction.
[0067] Specifically, the co-solvent includes any one or a combination of several of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or acetonitrile; the co-solvent is used to adjust the overall viscosity of the precursor solution so that it can smoothly penetrate into the pores of the composite framework at all scales during the wetting process, while promoting the full dissociation of lithium salt in the solution.
[0068] Specifically, plasticizers include any one or a combination of several of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, succinic acid, or glutaronitrile. After polymerization and curing, plasticizers remain in the polymer electrolyte network, reducing the crystallinity of polymer segments and maintaining their mobility.
[0069] It should be understood that the precursor solution obtained after mixing the precursor solution fully penetrates into the pores of the composite skeleton in liquid form during the wetting stage. During the thermosetting stage, while the monomers polymerize into a solid polymer network, lithium salt, cosolvent and plasticizer are uniformly distributed in the network, together forming a composite solid electrolyte membrane with ion conduction function.
[0070] It should be understood that, in order to verify that the composite solid electrolyte prepared by this method can solve the problems of high interfacial impedance and weak bonding between the filler and polymer matrix in existing solid electrolytes, the following experimental example is first conducted: Experimental Example 1: This experimental example is based on the preparation method described in the specification, using a polyimide / polyvinylidene fluoride blended fiber membrane as the matrix and zeolite imidazole ester backbone-67 as the metal-organic framework material. First, polyimide and polyvinylidene fluoride were dissolved in N,N-dimethylacetamide at a mass ratio of 1:1 to prepare a blending spinning solution with a total polymer concentration of 15 wt%. The solution was stirred at room temperature for 12 h until completely dissolved, resulting in a homogeneous polyimide / polyvinylidene fluoride blended spinning solution. Then, the above blended spinning solution was injected into an electrospinning apparatus, and electrospinning was performed under the conditions of an ambient temperature of 25℃, a voltage of 18 kV, a receiving distance of 15 cm, and a feeding speed of 0.8 mL / h to obtain a polyimide / polyvinylidene fluoride blended fiber membrane. The obtained fiber membrane was vacuum dried at 60℃ for 12 h to remove residual solvent. Next, the polyimide / polyvinylidene fluoride blended fiber membrane was immersed in a 3 mol / L potassium hydroxide aqueous solution and treated at 50℃ for 30 min. The surface-treated polyimide / polyvinylidene fluoride blended fiber membrane was then immersed in a solution containing 6.985g of cobalt nitrate hexahydrate and 100mL of methanol for 30min for ion exchange, so that cobalt ions could complex and anchor with carboxyl groups and oxygen-containing functional groups on the fiber surface. Subsequently, it was removed and immersed in a solution containing 15.76g of 2-methylimidazole and 100mL of methanol to allow zeolite imidazole ester backbone-67 to grow in situ on the fiber membrane surface. After stirring gently at room temperature for 24h, it was removed, rinsed with methanol, and vacuum dried at 60℃. It was then cut into 18mm diameter discs to obtain the polyimide / polyvinylidene fluoride@zeolite imidazole ester backbone-67 composite backbone. Subsequently, a precursor solution was prepared by dissolving 1 mol / L lithium bis(trifluoromethanesulfonyl)imide and 0.1 wt% azobisisobutyronitrile in a mixed solvent of hexafluorobutyl acrylate, N,N-dimethylacetamide, and propylene carbonate in a volume ratio of 9:1:3. The solution was stirred until completely dissolved to obtain the precursor liquid. Finally, 100 μL of the precursor liquid was injected into the obtained polyimide / polyvinylidene fluoride@zeolite imidazole ester framework-67 composite framework and allowed to stand for 24 h to allow the precursor liquid to fully wet and penetrate into the fiber gaps and metal-organic framework nanopores. Then, in-situ thermal polymerization was carried out at 70 °C for 10 h to obtain a composite solid electrolyte membrane, which was designated as sample S1.
[0071] Comparative Example 1 The difference between Comparative Example 1 and Experimental Example 1 is that the polyimide / polyvinylidene fluoride blended fiber membrane was replaced with a single polyimide fiber membrane, while all other conditions were the same as in Experimental Example 1. The resulting composite solid electrolyte membrane was designated as sample D1.
[0072] Comparative Example 2 The difference between Comparative Example 2 and Experimental Example 1 is that the polyimide / polyvinylidene fluoride blended fiber membrane was replaced with a single polyvinylidene fluoride fiber membrane, while all other conditions remained the same as in Experimental Example 1. The resulting composite solid electrolyte membrane was designated as sample D2.
[0073] Experimental Example 2 The difference between Experiment 2 and Experiment 1 is that the solute in the metal salt solution was replaced by zinc nitrate instead of cobalt nitrate, the organic ligand was replaced by 2-methylimidazolium instead of terephthalic acid, and the in-situ grown metal-organic framework material was replaced by metal-organic framework-5 (MOF-5) instead of zeolite imidazolium ester framework-67. All other conditions were the same as in Experiment 1. The resulting composite solid electrolyte membrane was designated as sample S2.
[0074] Experimental Example 3 The difference between Experiment 3 and Experiment 1 is that the monomer containing polar groups was replaced by methyl methacrylate instead of hexafluorobutyl acrylate. All other conditions were the same as in Experiment 1. The resulting composite solid electrolyte membrane was designated as sample S3.
[0075] Experiment Example 4 The difference between Example 4 and Experiment 1 is that the mass ratio of polyimide to polyvinylidene fluoride in the blended spinning solution was adjusted from 1:1 to 7:3, while the other conditions were the same as in Experiment 1. The resulting composite solid electrolyte membrane was designated as sample S4.
[0076] Experimental Example 5 The difference between Example 5 and Experimental Example 1 is that the polymer combination used in the blend spinning was replaced by polyimide / polyvinylidene fluoride with polyimide / polyacrylonitrile (mass ratio 1:1), and all other conditions were the same as in Experimental Example 1. The resulting composite solid electrolyte membrane was designated as sample S5.
[0077] The composite solid electrolyte membranes in samples S1, S2, S3, S4, and S5 from the above experimental examples, as well as samples D1 and D2 from the comparative examples, were assembled into coin cells and subjected to the following electrochemical performance tests.
[0078] Ionic conductivity testing: A coin cell was assembled using a stainless steel-composite solid electrolyte-stainless steel structure, and electrochemical impedance spectroscopy (EIS) was measured using an electrochemical workstation. The test frequency range was 0.1 Hz to 1 MHz, and the amplitude was 10 mV. The ionic conductivity was calculated using the formula σ = L / (R × S), where L is the thickness of the electrolyte film, R is the bulk resistance obtained from the impedance spectrum, and S is the electrode area.
[0079] Table 1: Comparison of Ion Conductivity
[0080] Table 1 shows that the composite solid electrolyte membrane in Experimental Example 1 is a polyimide / polyvinylidene fluoride blend fiber @ zeolite imidazole ester backbone-67. The composite solid electrolyte membrane in Comparative Example 1 is also a polyimide @ zeolite imidazole ester backbone-67. The ionic conductivity of Experimental Example 1 is 1.04 × 10⁻⁶. - The concentration of S / cm is higher than that of Comparative Example 1, which is 3.94 × 10³. -4 S / cm and 2.54×10 in Comparative Example 2 -4 The S / cm ratio indicates that the composite fiber membrane prepared by the blend spinning method has significant advantages in terms of uniformity of metal-organic framework loading and dense coating due to the multiphase chemical interface formed by microphase separation, thereby improving the ionic conductivity of the final solid electrolyte. Specifically, the ionic conductivity of Comparative Example 1 is higher than that of Comparative Example 2, indicating that the structural stability provided by polyimide as a rigid framework and the strong complexing ability of polyimide surface carboxyl groups for metal ions are superior to the flexible and polar interface provided by polyvinylidene fluoride alone in terms of metal-organic framework growth and ion conduction. Specifically, the experimental results of Examples 1-5 show that all process parameters affect the ionic conductivity of the composite solid electrolyte membrane. In Experiment 2, the conductivity decreased after replacing the zeolite imidazole ester backbone-67 with MOF-5. In Experiment 3, the conductivity decreased after replacing the fluorinated monomer with methyl methacrylate, indicating that the pore structure formed by the coordination of the imidazole group and cobalt ions in the zeolite imidazole ester backbone-67 is more conducive to lithium ion conduction. In Experiment 4, the conductivity decreased after adjusting the mass ratio of polyimide to polyvinylidene fluoride from 1:1 to 7:3, indicating that reducing the flexible polyvinylidene fluoride phase reduces the multiphase interface density and the number of active sites. In Experiment 5, the conductivity decreased after replacing polyvinylidene fluoride with polyacrylonitrile, indicating that the synergistic anchoring effect of the oxygen-containing functional groups and carbon-carbon double bonds formed by alkali treatment of polyvinylidene fluoride and the wettability advantage of the flexible segments are superior to the hydrolysis products of polyimide.
[0081] Understandably, the blended fiber membrane achieves a synergistic improvement in ionic conductivity through the synergistic effect of polyimide providing mechanical framework support and heat resistance, and polyvinylidene fluoride providing flexibility and a polar interface. In the blended fiber membrane, the differences in solubility between polyimide and polyvinylidene fluoride lead to microphase separation, forming a multiphase interface of polyimide-rich and polyvinylidene fluoride-rich phases. This provides a chemically differentiated distribution of active sites, which is beneficial for the uniform and dense coating of the metal-organic framework—a structural advantage that cannot be achieved with single polymer fibers.
[0082] The second embodiment of the present invention also provides a composite solid electrolyte membrane, which is prepared by the above-described method for preparing composite solid electrolytes. The composite solid electrolyte membrane includes a composite framework and a filler. The composite framework includes a fiber membrane layer and a growth layer. The fiber membrane layer is composed of several overlapping fibers in a three-dimensional network structure. Pores are provided on the fiber membrane layer. The growth layer covers the surface of the fibers. The growth layer is a layered structure of metal-organic framework material anchored to the surface of the fibers by coordination bonds. Complexation anchoring points are provided on the inner wall of the pores. The filler is provided in at least a portion of the pores. The filler is a mixture of materials containing polar groups. The polar groups are fixed to the inner wall of the pores formed by the growth layer by chemical bonding with the coordination bonds in the growth layer.
[0083] Understandably, in the composite solid electrolyte membrane provided in this example, the fiber membrane layer consists of a three-dimensional network structure composed of several overlapping fibers, which provides a continuous mechanical support framework for the entire electrolyte membrane. The growth layer, as a metal-organic framework material, is a layered structure anchored to the fiber surface through coordination bonds, uniformly covering the surface of each fiber. Complexation anchoring points are provided on the inner wall of the pores, and the filler material fills at least part of the pores. The filler material is a mixture containing polar groups, which are chemically bonded to the inner wall of the pores through coordination bonds in the growth layer.
[0084] In the solid electrolyte membrane, the fibers and growth layer are chemically anchored through coordination bonds between the metal-organic framework (MOF) material and the active sites on the fiber surface. The growth layer and filler are chemically bonded through coordination interactions between the polar groups of the polymer chains in the filler and the metal sites of the MOF in the growth layer. Since the strength of chemical bonding is significantly greater than physical forces, there are no physical interfaces between the filler and growth layer, or between the growth layer and fibers, allowing for relative slippage or peeling. Therefore, the resistance encountered by lithium ions during cross-interface migration is reduced due to the tight interfacial bonding. Simultaneously, during battery charge-discharge cycles, when stress caused by electrode volume changes is transmitted to the electrolyte, the chemically bonded interfaces effectively resist interfacial cracking and phase separation caused by stress concentration, maintaining the relative position between the composite framework and the filler, thereby preserving the structural integrity of the electrolyte membrane during long-term cycling. Therefore, the composite solid electrolyte membrane provided in this example improves both ion conductivity and long-term cycling structural stability, solving the problem of high interfacial impedance and weak bonding between the filler and polymer matrix in existing composite solid electrolytes due to reliance solely on physical bonding.
[0085] The third embodiment of the present invention also provides a solid-state battery, including a positive electrode, a negative electrode, and a composite solid-state electrolyte membrane, wherein the composite solid-state electrolyte membrane is disposed between the positive electrode and the negative electrode.
[0086] Understandably, the composite solid-state electrolyte membrane serves as an ion-conducting and separating layer between the positive and negative electrodes. In the composite solid-state electrolyte membrane, the fibrous skeleton and the metal-organic framework growth layer are chemically anchored through coordination bonds, and the growth layer and the filler are also chemically bonded through polar groups and coordination bonds, forming a continuous chemical network from the fiber surface to the filler inside the pores. This eliminates the interfacial defects in traditional physical blending methods where the filler and polymer matrix are only bound by weak van der Waals forces. Therefore, the impedance encountered by lithium ions during cross-interface migration is significantly reduced, and the battery exhibits high ionic conductivity and excellent rate performance.
[0087] The fourth embodiment of the present invention also provides an electronic device, the electronic device including a device body and a solid-state battery, the solid-state battery being disposed within the device body for providing electrical energy to the device body.
[0088] Understandably, the electronic device incorporates a solid-state battery as its power source. Due to the multiple chemical bonds between the composite solid-state electrolyte membrane within the solid-state battery and between the fibers and the growth layer, and between the growth layer and the filler, the solid-state battery possesses high energy efficiency and high safety. High ionic conductivity and low interfacial impedance endow the battery with rapid charge and discharge capabilities, enabling the electronic device to support high-current charge and discharge, and shorten charging time. Electronic devices employing this solid-state battery feature fast charging, durability, and high safety.
[0089] In this invention, the electronic device may include, but is not limited to, portable consumer electronic devices, smart mobile terminals, electric vehicles, energy storage systems, or wearable devices. For example, the electronic device may be a smartphone, tablet computer, laptop computer, smartwatch, wireless headset, electric bicycle, electric motorcycle, electric vehicle, hybrid vehicle, drone, portable energy storage power supply, home energy storage system, or base station backup power supply.
[0090] The foregoing has provided a detailed description of a composite solid electrolyte membrane and its preparation method, as well as a solid-state battery and electronic device disclosed in the embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention. Any modifications, equivalent substitutions, and improvements made within the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that: The preparation method of the composite solid electrolyte includes the following steps: A first type of polymer, a second type of polymer, and a co-spinning solvent are provided as raw materials. The first type of polymer, the second type of polymer, and the co-spinning solvent are mixed and then subjected to electrospinning treatment to obtain a blended fiber membrane. A surface treatment agent is provided to treat the surface of the blended fiber membrane to form active sites on the surface of the blended fiber membrane; A metal salt solution is provided, and the blended fiber membrane that forms active sites is immersed in the metal salt solution so that metal ions exchange with the active sites and the active sites become metal ion growth points. An organic ligand solution is provided. After the blended fiber membrane is taken out of the metal salt solution, it is immersed in the organic ligand solution. The organic ligands in the organic ligand solution undergo coordination reactions at the metal ion growth points to form a chain-like growth layer. Unreacted organic ligand solution was removed from the blended fiber membrane to obtain a composite framework with a network structure; as well as A precursor solution is provided, and the composite skeleton is immersed in the precursor solution and then cured to obtain a composite solid electrolyte membrane.
2. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that: Electrospinning is used to obtain blended fiber membranes, including: A cospinning solution is obtained by mixing a first type of polymer, a second type of polymer, and a cospinning solvent. The cospinning solution is then immersed in an electrospinning apparatus. The electrospinning apparatus is used to spin fibers on rollers at an ambient temperature of 20℃-30℃ and a voltage of 15kV-25kV. After spinning, the fibers are dried to obtain a blended fiber membrane. The first type of polymer may include polyimide or polyacrylonitrile; the second type of polymer may include polyvinylidene fluoride or cellulose; and the cospinning solvent may include any one or a combination of several of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetone, butanone, tetrahydrofuran, ethyl acetate, dichloromethane, chloroform, or acetonitrile. The mass ratio of the first type of polymer to the second type of polymer in the blended fiber membrane is 1:(1-1.5).
3. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that: The active site includes one or more of carboxyl, hydroxyl, amino, amide, or carbon-carbon double bonds; and / or the surface treatment agent includes any one of an alkaline solvent, an oxidation treatment solution, or a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution; and / or the solute in the metal salt solution includes any one or a combination of several of cobalt nitrate, zinc nitrate, zinc acetate, copper nitrate, zirconium chloride, zirconium oxynitrate, cobalt sulfate, cobalt chloride, or copper chloride; the solvent of the metal salt solution includes any one or a combination of several of methanol, ethanol, water, N,N-dimethylformamide, or N,N-dimethylacetamide; wherein the alkaline solvent is any one or a combination of several of potassium hydroxide or sodium hydroxide; the oxidation treatment solution is any one or a combination of several of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxygen radical / sodium hypochlorite / sodium chlorite combined oxidation system, nitric acid, sulfuric acid, potassium permanganate, or hydrogen peroxide.
4. The method for preparing the composite solid electrolyte as described in claim 3, characterized in that: The formation of active sites on the surface of the blended fiber membrane includes: When the raw material of the blended fiber membrane includes polyimide, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 20℃-60℃ for 30 minutes-120 minutes to open the imide ring of the polyimide to generate carboxyl and amide groups. Both carboxyl and amide groups serve as active sites. When the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 40℃-80℃ for 10 minutes-60 minutes to introduce carbon-carbon double bonds and oxygen-containing functional groups on the surface of polyvinylidene fluoride. Both carbon-carbon double bonds and oxygen-containing functional groups serve as active sites. When the raw material of the blended fiber membrane includes polyvinylidene fluoride, the surface treatment agent is tris(hydroxymethyl)aminomethane-hydrochloric acid buffer. The blended fiber membrane is immersed in tris(hydroxymethyl)aminomethane-hydrochloric acid buffer and treated at 40℃-80℃ for 12-48 hours to introduce amino and hydroxyl groups onto the surface of polyvinylidene fluoride. Both amino and hydroxyl groups serve as active sites. When the raw material of the blended fiber membrane includes polyacrylonitrile, the surface treatment agent is an alkaline solvent. The blended fiber membrane is immersed in the alkaline solvent and treated at 30℃-70℃ for 1-12 hours, causing the cyano groups of polyacrylonitrile to hydrolyze into carboxyl and amide groups, both of which serve as active sites; and When the raw material of the blended fiber membrane includes cellulose, the surface treatment agent is an oxidation treatment solution. The blended fiber membrane is immersed in the oxidation treatment solution and treated at 20℃-40℃ for 2-24 hours to oxidize the hydroxyl groups of cellulose to carboxyl groups. Both carboxyl and hydroxyl groups serve as active sites.
5. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that: The formation of a growth layer through coordination reactions at metal ion growth sites includes: An alcohol solvent and a metal framework material are provided. The alcohol solvent and the metal framework material are mixed to form an organic ligand solution. A composite fiber membrane with metal ion growth points on its surface is immersed in the organic ligand solution and reacted at 20℃-40℃ for 2 hours-24 hours. The organic ligands in the organic ligand solution undergo a coordination reaction with the metal ions on the surface of the composite fiber membrane to form a growth layer on the metal ion growth points. The metal framework material includes any one or a combination of several of the following: zeolite imidazole ester framework-8, zeolite imidazole ester framework-67, copper benzotricarboxylic acid framework-1, zirconium terephthalic acid framework-66, zeolite imidazole ester framework-7, and zeolite imidazole ester framework-90.
6. The method for preparing the composite solid electrolyte as described in claim 1, characterized in that: The composite solid electrolyte membrane is obtained by immersing the precursor solution into the composite framework and then curing it. A precursor solution is obtained by mixing a monomer containing a polar group, a thermal initiator, a lithium salt, a cosolvent, and a plasticizer. The composite fiber skeleton with a mesh structure has pores. The composite fiber skeleton is immersed in a precursor solution and left to stand at 20℃-40℃ for 0.5 hours-48 hours to allow at least a portion of the precursor solution to permeate into the pores of the composite fiber skeleton; and After standing, the composite fiber skeleton is heat-cured at 50℃-90℃ for 4-24 hours, so that the monomers containing polar groups in the precursor solution are polymerized and cured in the pores to obtain a composite solid electrolyte membrane.
7. The method for preparing the composite solid electrolyte as described in claim 6, characterized in that: The monomers containing polar groups include any one or more of the following: methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, glycidyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, acrylonitrile, vinyl acetate, fluorinated acrylates, or hexafluorobutyl acrylate; and / or The thermal initiator includes any one or a combination of several of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobiscyclohexylformonitrile, benzoyl peroxide, or diisopropyl peroxide; and / or The lithium salt comprises any one or a combination of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium dioxalate borate, or lithium trifluoromethanesulfonate; the lithium salt concentration is preferably 0.5 mol / L to 2 mol / L; and / or The co-solvent comprises any one or a combination of several of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or acetonitrile; and / or The plasticizer includes any one or a combination of several of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, fluoroethylene carbonate, succinate, or glutaronitrile.
8. A composite solid electrolyte membrane, prepared by the method for preparing a composite solid electrolyte as described in any one of claims 1-7, characterized in that: The composite solid electrolyte membrane includes a composite skeleton and a filler. The composite skeleton includes a fiber membrane layer and a growth layer. The fiber membrane layer is composed of several overlapping fibers and has a three-dimensional network structure. The fiber membrane layer has pores. The growth layer covers the surface of the fibers. The growth layer is a layered structure of metal-organic framework material anchored to the surface of the fibers through coordination bonds. The inner wall surface of the pores is provided with complexing anchor positioning points, and at least a portion of the pores are provided with the filler. The filler is a mixture of materials containing polar groups, and is fixed to the inner wall surface of the pores enclosed by the growth layer by chemical bonding between the polar groups and the coordination bonds in the growth layer.
9. A solid-state battery, characterized in that: It includes a positive electrode, a negative electrode, and a composite solid electrolyte membrane as described in claim 8, wherein the composite solid electrolyte membrane is disposed between the positive electrode and the negative electrode.
10. An electronic device, characterized in that: It includes a device body and a solid-state battery as described in claim 9, wherein the solid-state battery is disposed within the device body.